Grassroots Circular Economy: Community-Based Zero Waste Management in an Indonesian Traditional Market - Nunuk Supadmi; Muhfiatun Muhfiatun; Dinik Fitri Rahajeng Pangestuti (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2025)
This research proposes an integrative zero-waste model for traditional markets by combining Community-Based Participatory Research (CBPR), circular economy principles, and Islamic environmental ethics. The research was conducted at Nirmala Market, Yogyakarta, Indonesia, involving 76 traders, market managers, and members of the surrounding community. A qualitative CBPR approach is used, with data collected through observation, surveys, focus group discussions, and documentation, and analyzed using thematic and descriptive statistical analysis. Initial assessments identified critical challenges in waste management, particularly low environmental literacy, with all participants unable to recognise key recyclable materials (e.g., HDPE and multilayer plastics), while plastics made up 68% of total waste. These findings point to structural, behavioral, and ethical gaps in existing waste practices. Interventions are carried out through participatory waste sorting training, institutional strengthening, and organic waste processing through maggot cultivation. The results showed an increase in waste literacy and observable behavioral changes among traders. In addition, maggot cultivation operationalizes circular economy principles by converting organic waste into economically valuable outputs, thereby linking environmental management with local income generation. The study further conceptualizes zero-waste practices within the framework of Islamic ethics, emphasizing management (caliph), responsibility (amanah), and avoidance of environmental degradation (façade), which increases community engagement and sustainability of interventions. The model also shows the potential for scalability, supported by an estimated 211 kg/day of organic waste generated by the surrounding community. The study contributes to the literature by advancing integrated socio-technical and ethical models for waste management in traditional markets, offering theoretical enrichment and practical implications for sustainable development in developing countries.